Industrial training report: Perpustakaan Sultanah Nur Zahirah, Universiti Malaysia Terangganu / Siti Nur Aisyah Abd Wahab - Abd Wahab, Siti Nur Aisyah (Faculty of Information Management, 2018)
The purpose of this documentation is to report all activities conducted by the trainee during Industrial Training for about 5 months at Perpustakaan Sultanah Nur Zahirah (PSNZ). This industrial training report consist of 4 chapters and that are introduction, organization information, industrial training activities and industrial training reflection. In order to complete study, trainee needs to undergo 5 months of practical training in industry starting from 1 August 2018 until 31 December 2018. During the training, trainee got opportunity to learn the library management process. This report consists the details of training activities including daily tasks and special project. Lastly, the knowledge, skills, and experience gain during the practical training is the best method in order toprepare student to expose to the real working environment and also to be a good and better librarian in the future.